Historical and Social Factors in the Diversity of Arabic Literary Works - Ash Siddieqy, Muhammad Hasbi; Jihan Sabila; Rahma Maulidya Lathifa (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article aims to examine the historical and social factors that influence the diversity of Arabic literary works. Arabic literature, which spans a long period from the pre-Islamic era to the contemporary period, displays a rich variety in genres, themes, and linguistic styles. This study explores how historical conditions have shaped and influenced the development of Arabic literature. The method used is literature research, by collecting and analyzing sources relevant to the topic. Research findings from various literary theory books, journal articles, and cultural studies show that the diversity of literary works is greatly influenced by the historical and social contexts in which the works were produced. This influence can be observed in various aspects of literature, such as themes, language style, characters, settings, and narrative forms that reflect different periods and regions.